2019
DOI: 10.1039/c9dt01542f
|View full text |Cite
|
Sign up to set email alerts
|

The first water-based synthesis of Ce(iv)-MOFs with saturated chiral and achiral C4-dicarboxylate linkers

Abstract: Six different chiral and achiral alkane dicarboxylic C4-acids resulted in the formation of Ce(iv)-MOFs crystallizing in three different framework topologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…14 Other topologies, based on the same building units were reported later on. [15][16][17] Finally, the syntheses of mixed Zr-Ce MOFs and water based syntheses of Ce-MOF were recently presented. 18,19 Photocatalytic applications of MOFs have also been widely explored due to their semiconductor properties.…”
Section: Introductionmentioning
confidence: 99%
“…14 Other topologies, based on the same building units were reported later on. [15][16][17] Finally, the syntheses of mixed Zr-Ce MOFs and water based syntheses of Ce-MOF were recently presented. 18,19 Photocatalytic applications of MOFs have also been widely explored due to their semiconductor properties.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Avci-Camur et al [175] have described the water-based synthesis of two types of MOFs (Zr-MOFs and MIL MOFs) using metal acetylacetonate complexes as alternative source of metals. Most recently, Jacobsen et al [176] reported the successful water-based syntheses of a series of Ce (IV) -MOFs (UiO-66, CAU-41 and CAU-44) with three different topologies (fcu, body-centered cubic (bcu), and body-centered tetragonal (bct)) within 30 min via microwave-assisted reactions using six chiral and achiral alkane dicarboxylic C 4 -acids as ligands. In general, the development of a versatile method to fabricate different types of MOFs for future large-scale industrial production is desirable but challenging.…”
Section: Pcn Seriesmentioning
confidence: 99%
“…[15]. As a new type of nano porous material, comparing with activated carbon and zeolite, MOFs have been widely used in the fields of gas capture, storage and separation [16]; drug release [17]; optical, magnetic, electrical science [18]; catalytic science [19]; chiral resolution [20] and so on.…”
Section: Introductionmentioning
confidence: 99%